2018
DOI: 10.1016/j.rmed.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between exhaled carbon monoxide and asthma outcomes in Peruvian children

Abstract: Background: Asthma prevalence continues to increase in low and middle-income countries, presenting challenges in assessing asthma control in resource-poor settings. Previous studies suggest that exhaled carbon monoxide (eCO) is higher with asthma severity and lower with treatment. We hypothesized that eCO levels may be elevated in children with asthma, particularly in children with partially controlled or uncontrolled asthma in a low-resource setting in Lima, Peru. Methods: We compared average eCO levels betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
10
0
5
Order By: Relevance
“…Transportation and movement of vehicles produce and emit more than 70% of carbon monoxide. This gas interferes with the transport of oxygen in the human blood, leading to impaired cell respiration 42 . The O 3 criterion showed that it had an inverse relationship with the FR value, i.e., in lower values of this parameter, asthma attacks were more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Transportation and movement of vehicles produce and emit more than 70% of carbon monoxide. This gas interferes with the transport of oxygen in the human blood, leading to impaired cell respiration 42 . The O 3 criterion showed that it had an inverse relationship with the FR value, i.e., in lower values of this parameter, asthma attacks were more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on the application of gas signal messengers, like nitric oxide (NO) and carbon monoxide (CO), in allergy medicine is rapidly gaining more attention because they are easy and fast to measure and they have a close relationship with disease activity. 6,7 Hydrogen sulfide (H 2 S) is increasingly recognized as another important gasotransmitter. 8 Endogenous H 2 S has been proved to contribute to the pathophysiology of various airway diseases, including chronic obstructive pulmonary disease (COPD), asthma, and pulmonary fibrosis.…”
mentioning
confidence: 99%
“…The eCO levels in asthmatic children is significantly higher during the acute period than in the clinical remission period (P<0.05). The investigations of many international researchers (18,19) are consistent with this, and since eCO is easy to detect clinically, many advocate its use as a biomarker of asthma management. In the preschool children aged 3-5 years with simple asthma in this study, the eCO levels in the acute period were significantly higher than those in the clinical remission period (P<0.05).…”
Section: Discussionmentioning
confidence: 69%